Hematopoietic lineage diversification, simplified - Drissen, R; Nerlov, C (Elsevier, 2016)
Hematopoiesis is a complex process that requires a high degree of transcriptional diversification during lineage commitment and differentiation. de Graaf et al. (2016) have now generated a comprehensive gene expression dataset that allows cell-type-specific genes as well as associated transcription factor expression patterns to be readily identified.